2010
DOI: 10.4103/0255-0857.71835
|View full text |Cite
|
Sign up to set email alerts
|

IgG − Indirect fluorescent antibody technique to detect seroprevalence of Toxoplasma gondii in immunocompetent and immunodeficient patients in southern districts of Tamil Nadu

Abstract: The study has highlighted an overall seroprevalence of 11.71% with 12.57% in immunocompromised and 10.86% in immunocompetent patients respectively in a southern district, Tamil Nadu, which underlines the importance of screening of this parasite especially in the immunocompromised patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 9 publications
1
9
1
Order By: Relevance
“…Our recent previous report on seroprevalence toxoplasmosis in same districts of Tamil Nadu by in-house IFAT revealed 11.71% (Sucilathangam et al 2010) whereas in the present study, the prevalence was 13.14% by in-house IgG ELISA by using same set of samples. The in-house IgG ELISA was found to be 90% sensitivity and 100% specificity.…”
Section: Discussioncontrasting
confidence: 79%
See 3 more Smart Citations
“…Our recent previous report on seroprevalence toxoplasmosis in same districts of Tamil Nadu by in-house IFAT revealed 11.71% (Sucilathangam et al 2010) whereas in the present study, the prevalence was 13.14% by in-house IgG ELISA by using same set of samples. The in-house IgG ELISA was found to be 90% sensitivity and 100% specificity.…”
Section: Discussioncontrasting
confidence: 79%
“…There is no baseline data on seroprevalence and antibody titres of toxoplasmosis in various subpopulations in different parts of our country. In Tamil Nadu, various studies have done in northern districts (Bhatia et al 1974;Manikandan et al 2006) but so far not reported in southern districts except our earlier recent report (Sucilathangam et al 2010). Further complicating the situation, there are several commercial organizations that are promoting their products without proper background knowledge and baseline data from India.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Both IgG and IgM antibodies were enumerated in the patient's serum by Sandwich ELISA kits commercial available in market, according to manufacturer's instructions and methods described in Sucilathangam et al [10,11]. Number of samples collected and analyzed for HIV negative women were 605 and HIV positive women were 51.…”
Section: Enzyme Linked Immunosorbent Assay (Elisa)mentioning
confidence: 99%